Glycine Regulates Neural Stem Cell Proliferation During Development via Lnx1-Dependent Notch Signaling - Bekri, Abdelhamid; Liao, Meijiang; Drapeau, Pierre (Frontiers in Molecular Neuroscience, 2019)
During development of the zebrafish embryo, glycine signaling promotes the differentiation of neural stem cells. We found that glycine signaling suppresses the expression of Ligand of Numb X1 (lnx1), a gene of unknown function during neural stem cell differentiation that is selectively expressed in the embryonic central nervous system. As a consequence, Numb levels were stabilised and Notch activity (measured as her4.1 expression) was reduced, promoting neural stem cell differentiation. These consequent actions were blocked by knockdown of lnx1. In contrast, lnx1 overexpression increased neural stem cell proliferation and led to defects of neural tube closure at early stage of development. Thus, our data provide evidence that glycine/lnx1 signaling modulates neural stem cell proliferation by regulation of Notch signaling.